Analysis of Commercial and Fiscal Profits, Leverage on Profit Persistence at PT. Mighty True Great - Nurwahyuni Nurwahyuni; Faradita Farid; Anna Nurjanna; Indri Apriani; Muh. Asrullah Arifin; Vivianty Hemeto; Nungki Prawitasari; Muhammad Zidane Alfarizi (Universitas Muhammadiyah Makassar, 2024)
This study, titled